Pengaruh Promosi, Fasilitas dan Daya Tarik Wisata Terhadap Minat Berkunjung Wisatawan Ke Suwat Waterfall (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
Visiting interest is a person's motivation to visit destinations they have either previously visited or never visited before, and it is influenced by various factors such as promotion, facilities, and tourist attractions. Promotion is an activity that communicates the benefits of a product and persuades target customers. Facilities are service provisions designed to support the activities of tourists, while tourist attractions refer to anything that possesses uniqueness, beauty, or certain values capable of attracting visitors. The purpose of this study is to determine the influence of promotion, facilities, and tourist attractions on tourists’ visiting interest in Suwat Waterfall. This research uses probability sampling with a simple random sampling technique and involves 104 respondents. Data collection methods in this study include surveys, observation, interviews, documentation, literature study, and questionnaires. The results show that promotion, facilities, and tourist attractions each have a positive and significant partial effect on tourists’ visiting interest in Suwat Waterfall. The implication of this research is that promotion, facilities, and tourist attractions at Suwat Waterfall should be improved, so that tourists' visiting interest is expected to increase.